Analisis Kemampuan Berpikir Kritis Siswa Tentang Materi Larutan Elektrolit dan Non Elektrolit - Regina Kristia Ningrum; Ratman Ratman (Universitas Tadulako, 2021)
The purpose of this study was to describe students' critical thinking skills on the material of Electrolyte and Non-Electrolyte Solutions in class X SMA Negeri 6 Sigi. This type of research was descriptive quantitative. In the learning process, the teacher used Google Drive and the Whatsapp application as online learning media. The data collected was the form of critical thinking ability test results that obtained through giving questions in the form of online essays. Furthermore, the data were collected and analyzed based on indicators of critical thinking skills which including interpretation, analysis, inference, and evaluation. The results of data analysis on critical thinking skills of students of class X MIA 1 on the indicators of interpretation, analysis, inference, and evaluation were 51%, 41%, 42%, and 47%, respectively. The average result for all indicators of critical thinking ability of students in class X MIA 1 was 45%. For class X MIA 2, 51%, 39%, 36% and 41% respectively. Overall, the results of the critical thinking skills of class X student was 43.5%. This result shows that the critical thinking ability of students in the class X SMA Negeri 6 Sigi was in a low category